Teeth, Sticks, and Bricks: Calligraphy, Graphic Focalization, and Narrative Braiding in Eddie Campbell's "Alec." - Fischer, Craig; Hatfield, Charles (Substance: A Review of Theory & Literary Criticism, 2011)
This essay explores artist Eddie Campbell's "Alec: The Years Have Pants." Glasgow, Scotland native Campbell began his comics career in his early twenties after moving to England and was able to release his "Alec" series starting in the late 1970s. Alec's calligraphy is a feature of the comics that created a dashed-out diaristic intimacy due to its typically loose, sketchy and handwriting-like style. The drawing style of Campbell is also used to depict the selectiveness, blurriness and bias of the characters' memory.